Some peculiarities of the rotator cuff muscles - Holibka, Radomir; Holibkova, Alzbeta; Laichman, Stanislav; Ruzickova, Katherine (Biomedical papers, 2003)
The authors studied the origin, course and insertion as well as some peculiarities of RC muscles on 25 cadaverous fixed limbs. They discovered that RC muscles exchange muscle bundles and are secured by synovial sheaths. They described the articular muscles in all of the observed muscles, including the deltoid muscle, which significantly stretch the capsule of the glenohumeral joint. They expressed the opinion that the subscapular bursa enhances motions in the shoulder joint. Due to the possibilities of arthroscopic diagnostic and treatment methods, they are convinced that more attention must directed to this issue from both the morphological and functional perspective.
Keywords: Shoulder joint / Rotator cuff muscles / Synovial sheaths / Muscular bursas